Pancake Kidney With Obstructed Moiety: A Rare Renal Fusion Anomaly - Julio Slongo; Lucas R. Wiegand (Urology Case Reports, 2017)
Renal fusion abnormalities are rare. Even more rare is pancake kidney. We present a case of a 28-year-old male with symptomatic obstruction of a non-functioning moiety of a pancake kidney. He underwent ureterectomy with a finding of only atretic renal parenchyma at exploration. He recovered well and had resolution of his pain at 3-month follow-up.